Perceived Stressors, Social and Emotional Competences and Metacognition in Argentine Secondary School Teachers: Qualitative Description and Identification of Profiles - Giuliani, María Florencia (2026)
Objective. To identify the stressors perceived as most challenging by secondary school educators (Study 1) and to explore the associations between those stressors and social-emotional competencies and metacognition about teaching (Study 2). Method. Two studies were carried out. The first had a qualitative design, collecting narratives about stressful experiences (n = 75), content analysis was performed. The second study was quantitative, non-experimental, cross-sectional (n = 88) and surveys were applied on CSE, metacognition and stress. Multiple correspondence analysis was applied. Results. The most frequent stressors involve interactions with members of the educational community (Study 1). Two profiles of stressors were identified, classroom and community. Emotional self-regulation was associated with lower perceived stress, and evaluation as a facet of metacognitive awareness was associated with greater stress (Study 2). The results obtained support the need for interventions differentiated with an integrative theoretical framework.